2013
DOI: 10.1097/sla.0b013e318269d25d
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Surgery in Patients With Severe Acute Pancreatitis Managed by the Step-Up Approach

Abstract: PCD reversed sepsis in 62% and avoided surgery in 48% of the patients. Reversal of sepsis within a week of PCD, APACHE II score at first intervention (PCD), and organ failure within a week of the onset of disease could predict the need for surgery in the early course of disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
104
6
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(126 citation statements)
references
References 33 publications
14
104
6
2
Order By: Relevance
“…Also, management of infected or symptomatic collections needs interventions in the form of percutaneous drains or endoscopic/surgical necrosectomy/ drainage. 9,10 It is not clear if these interventions predispose to hemorrhagic complications in such patients. Systematic studies on gastrointestinal bleeding in acute pancreatitis are few and have not addressed the issue of intervention predisposing to occurrence of bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…Also, management of infected or symptomatic collections needs interventions in the form of percutaneous drains or endoscopic/surgical necrosectomy/ drainage. 9,10 It is not clear if these interventions predispose to hemorrhagic complications in such patients. Systematic studies on gastrointestinal bleeding in acute pancreatitis are few and have not addressed the issue of intervention predisposing to occurrence of bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…Success of percutaneous drainage is directly Babu et al 23 showed that percutaneous drainage reverted sepsis in 62% of patients and 48% did not need necrosectomy. These authors described a high rate of success with only drainage, in relation to others in literature.…”
Section: Predictive Factors Of Success Of Percutaneous Drainagementioning
confidence: 99%
“…Die Mortalität wurde durch dieses sequenzielle Vorgehen nicht reduziert (19 vs. 16%). Babu et al [37] evaluierten in einer erst kürzlich erschienenen Studie dieses sequenzielle Vorgehen für 70 Patienten mit nekrotisierender Pankreatitis. 55% der Patienten konnten dabei lediglich mittels intensivmedizinischer Behandlung und interventionellen Drainagen behandelt werden.…”
Section: Spezielles Vorgehen Bei Bestimmten Krankheitsbildernunclassified